Estudo cromossômico em gafanhotos do gênero Temnomastax Rehn & Rehn (Orthoptera, Caelifera, Eumastacidae, Temnomastacinae) - EDUARDO BRONCA BERNAVA (2025)
Eumastacidae is a family of grasshoppers with 255 described species, of which only 16 have some cytogenetic data, with only description by conventional staining. These works demonstrated a high variability in diploid number and chromosome morphology, despite having the conserved sex chromosome system (SCS) of the X0/XX type. However, this low amount of chromosomal data and the use of only conventional staining restrain the discussions about the comparison between species and karyotypic evolution in this family. The aim of this study was to characterize four species belonging to the genus Temnomastax: T. hamus, T. otavioi, T. ricardoi, and T. tigris. In this study, the species were analyzed by conventional staining (3% Giemsa), and, for the first time in the Eumastacidae family, with other cytogenetic techniques: C-banding, for visualization of the constitutive heterochromatin regions; fluorochrome DAPI, for the characterization of the DNA composition; and fluorescence in situ hybridization for localization of regions containing 28S rDNA genes and telomeric sequences. The four species presented the same diploid number, 2n♂ = 25 and 2n♀ = 26, chromosome morphology, with the first pair subtelocentric and the remaining of the elements telocentric, and SCS (X0/XX). However, some individualities were noticed in some species, T. otavioi presented a polymorphism for pericentric inversion on pair 4, while a B chromosome was observed in one female of T. hamus. Furthermore, the quantity, location and composition of the interstitial heterochromatin regions varied among the species. Hybridization signals with the telomeric probe were observed in the telomere region in all four species and, with the exception of T. hamus, in several interstitial sites. The location of the 28S rDNA was terminal in all species, however its distribution varied between 4 and 12 bearing chromosomes. The results show that although the four species have the same diploid number, chromosome morphology and SCS, the organization of specific chromosome regions is different. Several mechanisms may have occurred for the change in the number and position of the regions evidenced in this study, which is the main factor for the karyotypic differentiation between the species. Furthermore, each used technique allowed species distinction, therefore, we suggest the regions highlighted by these techniques as cytogenetic markers for the species in this genus.